Flexible PVDF Thin Film as Piezoelectric Energy Harvester - Izwan Nordin, Norfaizul; Ab Rahim, Rosminazuin; Aini Md Ralib, Aliza (Institute of Advanced Engineering and Science, 2019)
This aim of this paper is to study the potential of Polyvinylidene Fluoride (PVDF) polymeric piezoelectric film as an energy harvester for daily application use. PVDF offers several advantages over other piezoelectric materials such as high chemical strength and stability, high piezoelectric properties and biocompatible. Several investigations were carried out in this project which comprises of simulation, functionality test and application test. For functionality test, the highest voltage produced for a single film PVDF is 0.368 V which charges up a capacitor to 0.219 V in one minute. The highest voltage produced by multiple PVDF films is 1.238 V by stacking 10 films of PVDF in parallel which charges up to 0.688 V in one minute. For application test, 5 pieces of PVDF films were attached to a glove to generate some voltage during fingers bending activity. The highest output voltage recorded is 0.184 V which stores 0.101 V in a capacitor after 200 times of hand bending and releasing. As a conclusion, PVDF has a good potential as an alternative energy for daily application use. Combination of PVDF energy harvester system with proper power optimization circuit will open up rooms of research opportunities in energy harvester system with promising prospect in self-powered wireless electronics devices for Internet-of-Things application.